ANALISIS DISPARITAS PEMBANGUNAN EKONOMI ANTAR KECAMATAN DI KOTA MEDAN - Astari Khairunnisa; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2015)
This research aimed to determine the pattern of economic development of each district, the level of disparity (inequality) economic development that occurs among districts, and the appropriate strategies and policies in problem solving disparity (inequality) economic development in Medan. This research uses Typologi Klassen analysis, Williamson Index analysis, and descriptive analysis.The results of Typologi Klassen analysis during the periode 2001-2005 and 2006-2010 classify 3 districts included in quadrant I (fast forward and fast growing) , 5 districts included in quadrant II (forward but depressed), 2 districts included in quadrant III (fast growing), 4 districts included in quadrant IV (relatively underdeveloped) and 7 districts have been changed the pattern of economic development. Analysis Williamson Index shows that the value are low with an average index is 0.16994. So the strategies and policies an needed in the problem solving of disparity or inequality that occurred in Medan.Keywords : Economic Development Disparity, Klassen Typologi, Williamson Index